2012
DOI: 10.2319/122011-780.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic expression of MMP-Matrix-mettalo-proteinases (MMP-1 and MMP-13) as a function of anterior mandibular repositioning appliance on the growth of mandibular condylar cartilage with and without administration of Insulin like growth factor (IGF-1) and Transforming growth factor-B (TGF-β)

Abstract: Objective: To determine if the mandibular condylar cartilage (MCC) will grow with and without mandibular anterior repositioning appliances with the administration of insulin-like growth factor (IGF-1) and transforming growth factor-b (TGF-b). Materials and Methods: Twenty-four growing New Zealand rabbits were divided into three groups: a group with saline injection in the temporomandibular joint, a group that received anterior positioning appliance, and a group that received injection of growth factors as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Then we found that ADSCs could also inhibit the apoptosis of chondrocytes by adjusting the expression of caspase-3, which showed us that ADSCs could promote the proliferation of chondrocytes from another point of view. Some studies have showed that matrix metalloproteinase can damage the regeneration of chondrocytes to some extent [28], so we tested the effect of ADSCs on MMP3 and MMP13. The results confirmed that ADSCs and TGF- β 1 can inhibit the expression of these two proteins to a certain extent, which can also indicate that ADSCs play a role in promoting the regeneration of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Then we found that ADSCs could also inhibit the apoptosis of chondrocytes by adjusting the expression of caspase-3, which showed us that ADSCs could promote the proliferation of chondrocytes from another point of view. Some studies have showed that matrix metalloproteinase can damage the regeneration of chondrocytes to some extent [28], so we tested the effect of ADSCs on MMP3 and MMP13. The results confirmed that ADSCs and TGF- β 1 can inhibit the expression of these two proteins to a certain extent, which can also indicate that ADSCs play a role in promoting the regeneration of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular expression of MMP-1 was non-significantly increase in the active and the post-retention period reflecting the activity of interstitial collagenase (MMP-1 and MMP-8) due to increasing ages of rats at the end of experiment compared with early stage of experiment and with the control group [41]. Moreover, MMP-8 showed slight and nonsignificant increase in its intracellular expression in both retention and post-retention periods as act with MMP-1 by digesting a number of extracellular matrix and non-extracellular matrix protein [42].…”
Section: Journal Of Orthodontics and Endodontics Issn 2469-2980mentioning
confidence: 97%
“…In future, how about a pill to correct your malocclusion? Identifying molecular regulators of mandible and maxilla growth (Patil et al, 2012) may lead to pharmaceutical targets that better coordinate jaw outgrowth (Moreno Uribe and Miller, 2015). However, counter to a repu-tation as aberrant (Gremillion, 2006), most malocclusions are simply evidence of the phenotypic lability of the human jaw.…”
Section: Its Not What You Look Like But What You Chew That Countsmentioning
confidence: 99%